The Vietnam War - Barr, Roger, 1951- (San Diego, CA : Lucent Books, 1991)
Discusses the course of the Vietnam War from its early stages before American involvement to the 1974 ceasefire and its aftermath.
Includes bibliographical references (p. 107-108) and index.
Keywords: Vietnam War, 1961-1975.